Konsep Qana’ah Perspektif Hamka Dalam Mengatasi Stres Di Era Milenial - Seftha Meldi; Alfi Julizun Azwar; Deddy Ilyas (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
Qana'ah means being satisfied with what one has and not being greedy. It's about accepting what is enough. People who have qana'ah feel satisfied and are not afraid or doubtful, trust in Allah SWT's help without feeling annoyed when their desires are not fulfilled. The aim of this research is to discuss the concept of qana'ah from the Hamka perspective through a study of dealing with stress in the millennial era. The problem formulation and aim of this research is to find out about qana'ah according to Hamka and qana'ah according to Hamka in dealing with stress in the millennial era. In this research, qualitative methods were used with a library research approach. The data source used in this research is the Modern Sufism Book and is supported by relevant references. The results of this research explain the concept of Qana'ah teaching acceptance and gratitude, while mental health focuses on psychological well-being and the ability to overcome life's challenges. Both concepts emphasize contentment, balance, and harmony for a fulfilling life.